2010
DOI: 10.1590/s0100-83582010000400012
|View full text |Cite
|
Sign up to set email alerts
|

Seletividade do herbicida tembotrione à cultura do milheto

Abstract: RESUMO -O presente trabalho teve por objetivo avaliar a seletividade do herbicida tembotrione aplicado em pós-emergência na cultura do milheto. Foram realizados dois ensaios, avaliandose primeiramente o efeito do herbicida sobre três cultivares de milheto (ADR-300, ADR-500 e ADR-7010) em casa de vegetação. Posteriormente, o híbrido ADR-7010 foi submetido, no campo, a doses crescentes de tembotrione aplicadas em dois estádios de desenvolvimento das plantas (quatro e sete folhas completamente desenvolvidas). Em … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 14 publications
1
8
0
8
Order By: Relevance
“…Despite the rapid injuries recovery at 21 DAA, the authors have reported that trends evidenced at 7 DAA were maintained, indicating that applications accomplished in the earlier stages of sorghum crop development have provided the highest levels of crop injury, www.intechopen.com implying that herbicide tolerance increases as plants get older. Similar effects related to tembotrione applications in pearl millet have also been described (Dan et al, 2010c). In pear millet, higher tolerance occurred when tembotrione (75 g ha -1 ) was applied at the beginning of tillering, as compared to prior-tillering.…”
Section: Selectivity Of Tembotrione To Grain Sorghumsupporting
confidence: 69%
“…Despite the rapid injuries recovery at 21 DAA, the authors have reported that trends evidenced at 7 DAA were maintained, indicating that applications accomplished in the earlier stages of sorghum crop development have provided the highest levels of crop injury, www.intechopen.com implying that herbicide tolerance increases as plants get older. Similar effects related to tembotrione applications in pearl millet have also been described (Dan et al, 2010c). In pear millet, higher tolerance occurred when tembotrione (75 g ha -1 ) was applied at the beginning of tillering, as compared to prior-tillering.…”
Section: Selectivity Of Tembotrione To Grain Sorghumsupporting
confidence: 69%
“…Devido à sua grande adaptação e difusão no bioma dos cerrados, o milheto vem ganhando destaque nos últimos anos, especialmente após o lançamento de híbridos de alto potencial produtivo, oriundos do melhoramento genético (Dan et al, 2010). Além disso, a cultura apresenta boa produção de palhada, constituindose em importante opção para o sistema de plantio direto e na produção de forragem quando plantado em sucessão (Torres et al, 2008).…”
Section: Introductionunclassified
“…did not influence yield components or the biometrics of maize plants. On the other hand, Dan et al (2010) observed the importance of forage management in maize productivity and that competition among intercropped species should be suppressed.…”
Section: /8mentioning
confidence: 99%
“…Launched in Brazil for post-emergence use in maize crops, Tembotrione has shown a satisfactory performance in weed control, especially of grasses (Dan et al, 2010). However, there are few studies on the potential use of this herbicide in intercropping systems.…”
Section: Introductionmentioning
confidence: 99%